Soft tissue tumors occurring in the perinatal/infancy setting: 2nd part - Gavino Faa; Raf Sciot (Hygeia Press di Corridori Marinella, 2018)
In the second part, the following soft tissue tumors occurring in the perinatal period and/or in children and adolescents younger than 10 years, will be described: smooth muscle tumors, pericytic tumors, neurogenic tumors, vascular tumors and tumors of uncertain origin, including malignant extrarenal rhabdoid tumor and primitive myxoid mesenchymal tumor of infancy. For each entity, the following data are summarized: age of presentation, the most frequent localization, the typical macroscopic and microscopic findings, the immunohistochemical features and the molecular data wich play a relevant role in their diagnosis. Each tumor entity is described with a practical approach, with the aim that this review will help perinatal and pediatric pathologists in the differential diagnosis of a group of tumors that are diagnostically challenging, due to their rarity and to the frequent lack of specific morphological and immunohistochemical markers.